Optimizing of the specific power consumption of an ore grinding mill, taking into account the stability of its electric drive system - Baghdasaryan, Marinka; Hakobyan, Eduard; Vardanyan, Gor (Edelweiss Applied Science and Technology, 2025)
Rising energy costs and the alarming state of the environment are creating new problems for energy-intensive industrial enterprises. This is why energy saving is currently becoming an increasingly relevant issue in all areas of economic and social development. Of particular interest are energy-intensive technological processes, which are interconnected and operate under the influence of random factors. One example is the electric drive system of a drum mill, which powers the ore crushing process. This paper presents a new approach to optimizing the specific energy consumption of electric drive systems for ore crushing mills. The essence of this approach is that the formulated energy-saving problem considers system stability. This approach eliminates unnecessary energy costs for systems operating under nonstandard conditions while ensuring the production of high-quality products. Depending on the specific gravity of the crushed ore, a comparative analysis shows that energy savings of up to 34.4% can be achieved. The stabilization condition can be used to optimize the electromechanical mill system’s specific energy consumption, thereby improving operational efficiency.